Investigation of traffic accidents and contributing factors on desert roads: A case study of the Yazd-Kerman axis in central Iran (2015-2021) - Azam Tarfiei; Hamidreza Mehri; Reza Jafari Nodoushan; Farzan Madadizadeh (Archives of Trauma Research)
Background: Road traffic accidents are a significant contributor to global fatalities, resulting in substantial societal losses each year.Objectives: This study aimed to investigate the occurrence of desert road accidents and the factors associated with them along the Yazd-Kerman axis, located in central Iran.Methods: This analytical study utilized data from cases registered at the Naja Road Police Accident Registration Center in Yazd Province between 2015 and 2021. Road accidents were categorized into three types: fatalities, injuries, and economic losses. Multinomial logistic regression (MLR) was employed for inferential statistics. All statistical analyses were conducted using SPSS version 26, with the significance level set at 0.05.Results: The findings revealed that out of 5,468 accidents, 5.96% (n=326) resulted in fatalities, 51.74% (n=2,829) caused injuries, and 42.30% (n=2,313) led to financial losses. Most accidents involved Pride and Peugeot sedans (approximately 18%). The majority of accidents occurred among drivers aged 30–39 years (38.04%, n=2,080). Human factors, including the driver’s inability to control the vehicle (38.93%, n=2,129) and lack of attention (25.64%, n=1,402), were the most common causes of accidents. The results of the MLR showed that, in terms of injuries, drivers aged 20–29, 30–39, 40–49, and 50–59 years had significantly higher odds of injury compared to those aged over 60 years (OR=1.53, OR=1.59, OR=1.67, OR=1.85, respectively). The odds of injury in front-to-front collisions were approximately 34% higher than in other types of collisions (p=0.011, OR=1.34). However, the MLR did not identify a significant relationship between fatalities and any of the age groups or angle collisions (p>0.05).Conclusions: Human error was identified as the most common cause of traffic accidents, while injury severity was associated with driver age and the type of collision. Stricter enforcement of traffic laws by the police could play a crucial role in reducing road traffic accidents.